Front Cover: Comparison of the separation of proteins of wide‐ranging molecular weight via trilobal polypropylene capillary‐channeled polymer fiber, commercial superficiously porous, and commercial size exclusion columns. Issue 9 (9th May 2022) - Huang, Sisi; McClain, Ray T.; Marcus, Richard Kenneth
Abstract : DOI: 10.1002/jssc.202100891 The reversed‐phase (RP) separation of proteins, without size‐exclusion contributions, is affected on capillary‐channeled polymer (C‐CP) fiber stationary phases. Polyester C‐CP fibers are demonstrated to perform the rapid RP separation of peptides and proteins ranging in molecule weight of 1.44‐to‐660 kDa. Comparisons with commercial RP superficially porous and size exclusion columns designed for protein separations show that the across‐the‐board separation quality realized by the fibers is superior to the other column formats, with column material costs being far less than the standard columns.